Neovascular age‐related macular degeneration treated with ranibizumab or aflibercept in the same large clinical setting: visual outcome and number of injections. Issue 2 (18th August 2016) - Rasmussen, Annette; Sander, Birgit; Larsen, Michael; Brandi, Sara; Fuchs, Josefine; Hansen, Louise H.; Lund‐Andersen, Henrik
Abstract: Purpose: To study visual outcome and number of annual injections in treatment‐naïve patients with neovascular age‐related macular degeneration (nAMD) before and after a change in first‐line therapy from ranibizumab to aflibercept in a high‐volume clinical practice. Methods: This was a retrospective chart review of routine clinical practice. The study included 1027 treatment‐naïve patients, 559 of whom started intravitreal ranibizumab therapy in 2011–2012 and 468 of whom started intravitreal aflibercept therapy in 2013–2014, a fixed loading dose of three injections followed by a pro re nata treatment regimen used in both periods. Results: Snellen best‐corrected visual acuity (BCVA) at baseline and after one year was 0.23 and 0.31 (p < 0.0001), respectively, for patients treated with ranibizumab and 0.25 and 0.33 (p < 0.0001) for patients treated with aflibercept, last observation carried forward. The share of patients (73%) still in treatment with ranibizumab at year 1 had a baseline BCVA of 0.26 but 0.40 at year 1 (p < 0.0001), and the patients (75%) still in treatment with aflibercept at year 1 had a baseline BCVA of 0.28 but 0.42 at year 1 (p < 0.0001). Proportional visual gains for both cohorts were comparable for one year (p = 0.14). The number of injections given within year 1 including first injection was 6.9 for ranibizumab and 5.9 for aflibercept (p < 0.0001). In patients continuing treatment through year 1, the number of injections was 8.0 for ranibizumab and 6.6 for aflibercept (p < 0.0001). The two cohorts had similar cause‐of‐discontinuation profiles. Conclusion: Treatment of nAMD at a single centre in two sequential cohorts yielded comparable BCVA outcomes with 15% fewer injections of aflibercept compared to ranibizumab.